Impact of Exercise on Hemophilia - Zetterberg, Eva; Ljungkvist, Marcus; Salim, Maryem (Seminars in Thrombosis and Hemostasis, 2018)
Sports and strenuous exercise have traditionally been discouraged for people with hemophilia (PWH) because of the perceived risk of bleeding. In this review, studies investigating the pros and cons of exercise are presented, and although most studies are of low validity, the randomized trials that do exist tell us that PWH benefit from exercise in terms of improved muscular function, endurance, and quality of life and that increased bleeding does not seem to be an issue. The authors also review the studies that have analyzed the current physical status of PWH compared with the general population in different countries. Finally, they review the current knowledge on the effect of exercise on specific coagulation factors as well as on global coagulation and demonstrate that exercise increases factor VIII levels in healthy persons, all persons with hemophilia B (HB) and in persons with mild and moderate hemophilia A (HA). Further, the authors did not find any evidence that the global coagulation capacity, measured with thrombin generation or thromboelastographic methods, increases after exercise in severe HA or HB.
Keywords: exercise; hemophilia; endurance; quality of life; thrombin generation